The Travel Staff English Communication Problem A Survey At Look Lombok Tour & Travel 2021 - Muhammad Auliaurrahma; M. Afan; Nurul Bulqis (Departement of Mathematics Education, 2024)
This study aimed at finding out The Travel Staff English Communication problem A Survey At Look Lombok Tour & Travel 2021. The writer took one group tour of the population (group tour A with 22 guest) as the sample of this study. The data of the study were obtained from the observation, questionnaire, and interview and were analyzed using descriptive qualitative and quantitative method. The results showed that: 1) There were four kinds of communication failure in speaking office at Look Lombok Tour And Travel, Failure to convey the message correctly, with the occurrence was 22.7%; Failure to react to the message (40.9%); Failure to control the communication (18.1%); and Failure to understand the purpose of the message (18.1%); 2) There were two factors accounting for the causes of communication failure in the Speaking. They are internal factors, which consist of lack of self confidence, mental exhaustion, less of background knowledge, lack of vocal/voice control, and less of body movement and facial expression; and external factors that is including the factors on inattentive listener, uncomfortable environment, and lack of opportunity.